Investment in disaster resilience in the built environment - Perera, Srinath; Lill, Irene (International Journal of Strategic Property Management, 2016)
"Guest Editorial ‘Investment in disaster resilience in the built environment’."International Journal of Strategic Property Management, 20(3), p. 221-223